Development Favorable Area and Productivity Potential Evaluation Method of a Tight Oil Reservoir. (7th January 2021) - Wang, Shuping; Lai, Fengpeng; Wang, Kongjie; Li, Zhiping; Wang, Hong
Abstract : Tight oil resources have become the focus of unconventional oil and gas exploration and development. Well placement is an essential factor determining the development of a field. Oil wells should be located in the area with favorable criteria for development. These areas should be screened based upon oil and gas enrichment of the reservoir. The influencing factors and analysis theory of an enrichment area are summarized in this paper. Two types of methods evaluating areas favorable for tight oil and gas production are explained here as well, including model prediction and the combination of geological modeling and reservoir simulation. The area with favorable geological, engineering, and economic attributes has the best development potential. The productivity potential can be used as one basis for selecting areas favorable for production. Based on the previous concept of productivity potential, combined with the characteristics of a tight oil reservoir, this study modified the evaluation of productivity potential, and the calculated potential area was the priority for well placement. The modified equation of productivity potential comprehensively considers effective pore pressure, mobile oil saturation, porosity, permeability, effective thickness, distance from the boundary, and threshold pressure gradient. A tight reservoir was taken as an example for calculation, and the results of the modified method, original productivity potential method, and reserve abundance calculation method are discussed. Two new wells were arranged in the favorable areas obtained by different productivity potential evaluation methods, and the production was calculated under the same parameters for each method. The recovery of this area was 51.65%, which is 1.73% and 2.84% higher than that of the other two methods.